Phrasal Verbs through DDL - Gabriele Azzaro (Ricerche di Pedagogia e Didattica, 2012)
Two techniques are examined for teaching 10 Phrasal Verbs (PVs) to two groups of university students: dictionary presentation and concordance-based Data-Driven Learning (DDL). After checking their prior knowledge, 5 PVs were introduced via DDL, 5 via dictionary entries. The two techniques were compared, as well as the two groups of students, towards an assessment of DDL as a motivating and effective teaching aid. The results show that DDL can be a productive way to teach new lexical items and to consolidate old ones. The difference was statistically significant for the group which was smaller in size, more mature and working with corpus samples on screen rather than on paper. DDL, independently of classroom attendance, was a positive aid, whereas dictionary presentation was detrimental for some of the verbs involved.